Electron accepting porphycenes on graphene - Costa, Ruben Dario; Malig, Jenny; Brenner, Wolfgang; Jux, Norbert; Guldi, Dirk Michael (Advanced Materials, 2013)
The versatility of nanographene (NG) as an electron donor is demonstrated when integrated together with an electron accepting porphycene into a novel electron NG hybrid. This feature is further exploited in dye-sensitized solar cells (DSSCs), in which photoanodes (ZnO) reveal a cascade of electron flow as modus operandi. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.